The clinical characteristics of COVID-19 omicron variant infection in pregnant women and their neonates - Liu, Li-Li; Lin, Lv-Hua; Lin, Fen; Yang, Yi-Kang; Lin, Chun-Fan; Zhang, Lin; Huang, Yu-Chan; Liao, Yu-Wei; Zeng, Yan-Qing; Zeng, Guang-Kuan; Cao, Yan-Bin; Zhu, Rui-Zhen; et al. (Frontiers in Medicine, 2023)
Objective: The objective of this study was to analyze the clinical characteristics of pregnant women infected with the COVID-19 omicron variant and their neonates during the outbreak in Guangdong province, China.Method: The clinical data of pregnant women infected with the COVID-19 omicron variant and their neonates were retrospectively collected from two hospitals in Guangdong province. Results: Seventy-nine pregnant women infected with COVID-19 omicron variant and their 68 neonates were included in this study. The vast majority (86.1%) of pregnant women was in their third trimester of pregnancy. Of 79 pregnant women, thirty-nine cases were asymptomatic at the time of infection, and 40 mothers presented with mild manifestations of COVID-19. A total of 68 neonates (3 set of twins) from 65 mothers with COVID-19 were reviewed. According to the timing of birth, there were 10 (14.7%) preterm neonates. Two babies were born dead (intrauterine fetal death after 22 weeks of gestation). Of the live babies born (66 cases) from mothers with COVID-19, 9 newborns were lower weight, and one preterm case was born with respiratory distress and intubated, he recovered and developed normally. Conclusion: Although preliminary data suggests the risk of severe maternal and fetal complications from Omicron variant infection during pregnancy is lower than previous variants and Delta variant. Our study, which was conducted on a limited population sample, indicates that there is a possibility of severe complications, such as stillbirth, occurring in some fetal cases. These findings emphasize the need for continued attention from obstetricians.